2015
DOI: 10.1039/c4ra13363c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron field emission properties from hybrid nanostructures of graphene/Si tip array

Abstract: Highly efficient with excellent stability electron field emitters based on monolayer graphene coated on wellaligned Si tip (graphene/SiT) arrays fabricated by a simple transfer method are demonstrated. The graphene monolayer is coated on the Si tip array using a chemical vapor deposition process, while the SiTs are prepared through the etching process of a Si substrate. The novel heterostructure field emitter enhanced electron tunneling, as a result, exhibits a better emission property. In addition, the fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
(63 reference statements)
1
15
0
Order By: Relevance
“…For example, it has been reported the β of ZnO nanowire arrays is 1064, 33 Ag-nanoparticles-decorated ZnO nanorods is 1593, 34 metallic W nanowire bundles is 3563, 35 and graphene/Si tip arrays is 1000. 36 The resulting high enhancement factor is large due to high aspect ratio of our SiC nanostructures. Therefore, one-dimensional SiC nanowires are regarded as excellent field emitters ascribed to their high enhancement factor, low turn-on field and threshold field.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported the β of ZnO nanowire arrays is 1064, 33 Ag-nanoparticles-decorated ZnO nanorods is 1593, 34 metallic W nanowire bundles is 3563, 35 and graphene/Si tip arrays is 1000. 36 The resulting high enhancement factor is large due to high aspect ratio of our SiC nanostructures. Therefore, one-dimensional SiC nanowires are regarded as excellent field emitters ascribed to their high enhancement factor, low turn-on field and threshold field.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrons still need to transfer from the graphene to diamond at the tip of FLG-DNRs for field emission. It should be noted that in the case where graphene layers were coated on other kind of sharp templates such as Si-tip arrays [13], Si nano-rod arrays [15] and TiO 2 /diamond like carbon (DLC) films [41], the electrons conducted by the graphene layers could not be efficiently transferred to the emission sites due to the presence of larger barrier between the graphene and the underlying substrate materials. The graphene layers thus did not contribute much to FEE process for these materials, Here it is proposed that the formation of FLG on DNRs in-situ can enhance the overall FEE behavior of the materials because the electrons x can be transferred from the FLG to the DNRs easily, since the FLG was formed via in-situ annealing process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been reported on field emission from 2D materials such as graphene, graphene oxide, MoS 2 , MoSe 2 , WS 2 , and SnS 2 . While most of the early research suggested that the edge structure of 2D materials was more beneficial for field emission owing to its ultrahigh field enhancement factor, recent work has proposed using its surface as a field emitter with a hybrid structure consisting of 2D layered material supported on 1D nanowire (nanotip) . Geometrical modulation of the 2D material by the supporting nanowire has achieved enhanced field emission and high stability with 2D–1D hybrid structure.…”
Section: Introductionmentioning
confidence: 99%